Reconstruction of Marriage Law: Judges’ Progressive Reasoning Based on Maqāṣid in Addressing Divergent Interpretations in Indonesian Courts - Dikuraisyin , Basar; Sumarkan; Fatwa, Ah Fajaruddin; Ghozali, Muhammad Lathoif (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This study elucidates the rationale behind judges’ decisions to permit the registration of interfaith marriages, unregistered or underhanded marriages, and underage marriages. These three issues are subject to divergent opinions, reflecting the multi-interpretational nature of social reality. This study reveals the judicial process of law discovery in resolving rules subject to multiple interpretations. Employing a qualitative approach, primary data were obtained through interviews with judges from the Surabaya District Court and the Sumenep Religious Court. The findings indicate that in addressing cases characterized by ambiguity, lack of regulation, and multiple interpretations, judges rely not only on the Marriage Law but also on human rights provisions and the supreme legal authority of the Indonesian Constitution. Upon recognizing a legal vacuum, the judges opted to revert to higher norms, exercising judicial discretion. Reconstruction occurs when judges, encountering a lack of clear rules, prioritize human rights and the constitution over strict textual interpretations of fiqh. This progressive approach allows judges to balance contextual norms with the evolving objectives of sharia in society, thereby fostering justice in marital matters.